Efektivitas Pelaksanaan Mediasi Di Masa Pandemi Dalam Menekan Jumlah Angka Perceraian: Studi Kasus Pengadilan Agama Serang - Ahmad Harisul Miftah; Nurul Fauzi (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2021)
The rise of divorce rates is getting higher and continues to grow especially in pandemic times like this, one of which is due to economic factors. However, the divorce case must be in accordance with the mandate of Perma No.1 of 2016 which states the importance of mediation. The formulation of the problems in this study is: How is the implementation of mediation in the pandemic period in the settlement of divorce cases in the Serang Religious Court?, How is the role of mediator judges in reconciling and reducing the number of divorce rates during the pandemic in the Serang Religious Court?, and What are the obstacles faced by mediator judges in reconciling divorce cases during pandemics in the Serang Religious Court?. The conclusion of this study is that the procedure for the implementation of mediation in the Serang Religious Court is in accordance with Perma No.1 of 2016 on Mediation Procedures in Court and also implements health protocols in accordance with Presidential Instruction No. 6 of 2020 on Improving Discipline and Law Enforcement of Health Protocols in the Prevention and Control of Corona Virus Disease 2019, and mediator judges play an important role in reconciling and suppressing the number of divorces. This can be seen in the mediation report. The obstacles faced by mediator judges consist of several factors. Starting from the factors of divorce cases, litigated parties and factors from the mediator itself.